PAKs supplement improves immune status and body composition but not muscle strength in resistance trained individuals - Muzy Paulo C; Marques Fernando A; Lira Fabio S; Romero Frederigo G; Peres Rodolfo AN; Caperuto Érico C (Taylor & Francis Group, 2010)
Abstract Mixed formula supplements are very popular among recreational and professional weightlifters. They are usually known as PAKs and they are supposed to have a synergistic effect of their different nutrients. The purpose of this study was to determine the effects of chronic (4 weeks) PAKS supplementation in combination with strength training on body composition, immune status and performance measures in recreationally trained individuals with or without PAKs supplementation. Methods: Twelve male subjects (Placebo n = 6 and PAKs supplement n = 6) were recruited for this study. The body composition, one maximum strength repetition tests and immune status were assessed before and after 4 week supplementation. Our data showed that, 4 week PAK supplementation associated with strength exercise not was effective in change strength than compared with placebo group. However, we observed that, PAK supplement was able to improve immune status and reduced body composition when compared with placebo group. These results indicate that, a mixed formula supplement is able to improve immune status and body composition but not maximum strength in recreational strength trained subjects in a 4 weeks period.